Nitrofurans residue in broiler chicken meat which analysed by an HPLC - Widiastuti, Raphaella (Indonesian Animal Sciences Society, 2012)
Furazolidone (FZD), furaltadone (FTD), nitrofurantoin (NFT) and nitrofurazone (NFZ) are veterinary drugs that belong to the nitrofurans (NFs) group and employed as feed additives for growth promotion and theurapetic treatment of gastrointestinal infections caused by Eschericia coli and Salmonella spp. The occurrence of NFs in animal products will end to cause health problem in human consumed such food. This research conducted to study the analysis of NF residues in chicken meat by a high performance liquid chromatography (HPLC) and to study the occurrence of NFs residues in samples collected from traditional markets and supermarkets in Bandung, Bogor and Depok. The results of validation method on several parameters for each NF showed that the average of the relative standard deviation (RSD) from the precision study were 2.15 to 2.38%, the R2 values of the linearity study were 0.9964 to 0.9995; recoveries were 75.90 % to 91.50 % and the detection limits were 12.01 to 37.25 ng/g. The residual level of NFs for 42 field samples showed that 2 samples positive for NFZ (9.09 and 10.74 ng/g), 1 positive for NFT (10.46 ng/g), 4 positive for FTD (16.44 up to 27.21 ng/g) and none positive for FZD. Present results showed that analysis of NFs in broiler chicken meat can be done using an HPLC and the analysis results from field samples showed that these types of drugs were being used for broiler chicken production both as single and/or combination drugs, therefore it is necessary to raise public awareness to monitor the use of NF in livestock production in Indonesia. Kata Kunci: Detection, Residue, Nitrofurans, Chicken Meat, HPLC